Flood Management Strategy Based on Analysis of Regional Characteristics and Causal Factors in Kendari City - Agus Sakawuna, Wandira; Indra Setiawan, Budi; Perdinan (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2025)
Flooding is a disaster that causes environmental damage, economic losses, and social problem. Kendari City is one of the Indonesian cities that frequently experiences floods due to various factors, including high rainfall, land use changes, poor drainage conditions, and improper spatial management. This study aims to (1) assess the factors contributing to flooding, (2) analyze government governance and community participation in flood management, and (3) formulate an integrated flood management strategy. The methods used were descriptive analysis, spatial approach, SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM). The results showed that there is evidence of land use changes between 2013 – 2023 based on spatial image analysis. We found there were three sub-districts, which is categorized on high flood vulnerability namely Baruga, Kadia, and Kambu sub-districts. Based on the level of community preparedness parameters including knowledge and attitudes, emergency plans, early warning, and resource mobilization, Baruga belongs to the medium category (74.60%), while Kambu (57.42%) and Kadia (59.58%) were in low category. QSPM analysis recommends two priority strategies to reduce flood vulnerability namely accelerating drainage system improvements and replicating the Baruga model in other areas. Future research should focus on climate change-induced flood modeling, gender-sensitive vulnerability assessments, and economic loss estimation to enhance the effectiveness of flood management strategies.